Investigations on the [2,3]-Wittig Rearrangement of Chiral 4-Aminopropargyloxy Acetates to Novel α-Hydroxy-γ-amino Acids Containing an Allene Unit - Griebenow, Nils; Cumine, Florimond; Dilmac, Alicia M. (Synlett, 2015)
The [2,3]-Wittig rearrangement of propargyloxy acetates bearing a propargylic stereocenter opposite to the oxyacetic acid moiety gives α-hydroxy-γ-amino acids containing an allene unit under high stereocontrol. The resulting product displays a novel type of γ-amino acid with a potentially intriguing biological profile.
Keywords: Wittig rearrangement; propargyloxy acetates; γ-amino acids; allenes